Tydzień Miłosierdzia - Związek Caritas (Gdańsk). (Gdańsk : [s.n.], 1947)
Afisz z programem uroczystości 5-12.10.1947 w Gdańsku.
Keywords: Związek Caritas (Gdańsk) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie religijne